COMPARISON OF COMPETITIVE ACTIVITY INDICATORS AT 100 M DISTANCES OF LATVIAN AND EUROPEAN SWIMMERS - Jakubovskis, Germans; Solovjova, Jelena; Zusa, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The research aimed to study the performance characteristics of male and female finalists at a 100m distance when swimming at the Latvian swimming championships in a period from 2018 to 2020 (in the 50m pool). 262 final heats got analyzed. The results of the 3 best Latvian swimmers, males=36, and females-36, at each 100m distance (freestyle, breaststroke, backstroke, and butterfly) at championships in 2018, 2019, and 2020 have been analysed. The parameters for overcoming competitive distance: competitive result in the 100-meter distance; the start reaction time; time for the 15 meters mark; speed to the 15 meters mark; the time of the turn 5 meters up to the wall and 15 meters after the turn; underwater distance and time after the start and after turning; time of “clear” swimming. The obtained results were compared to the characteristics of overcoming the same competitive distance by the finalists of the European Championship 2016. As a result of comparative analysis, statistically, significant differences were found in such parameters of competitive activity as the overall result, overcoming of starting and turning parts, and the distance covered under water after the turn and start. Statistically significant differences were not found in the reaction time to the start signal and in the speed of “clear” swimming. The comparative analysis of the performance characteristics of the European Championships finalists showed possibilities for further improvements of Latvian swimmers. The aim: is to determine the performance parameters of the Latvian best swimmers and compare them with the same parameters of the finalists of the European Championship 2016.